"Conflict" or "Cooperation": A Study on The Spontaneous Order of Urban Public Space Development from The Perspective of Stakeholders. Issue 4 (December 2020) - Haoyu, Cheng
Abstract: Urban public space nourishes social relations, at the same time, the evolution and development of public space are also influenced by social relations. As an important factor affecting the development of public space, the interest relation of citizens presents the characteristics of conflict or cooperation in the occupation of public spaces and finally presents itself in the space form. Based on the point, this paper attempts to explain the evolution and development of urban public space from the perspective of stakeholders, and on this basis investigates the generation mechanism of spontaneous order in the development of urban public space. To meet the research aims, this paper first clarified the inherent meaning that space reflects and shapes social relations, and then selected a certain urban area of Jinan in northern China for the case study. Through the data collected from Google earth history images, interviews, and published reports, the evolution of the major public spaces in this case from 2003 to 2020 was objectively presented. On this basis, the author analysed the social relations, appeals, and actions of various stakeholder groups (such as local people and non-local traders) in different periods in this case, as well as the staged outcomes of their effects on the public space. Finally, a game model of stakeholders was established. The results indicated that the development of a city is a process that mitigates the conflict between social and public space resources. In the occupation of public space resources, the relationship between the stakeholders is dynamic: when the cost is high and the return is low, the stakeholders show a trend of "conflict"; when costs are low and returns are high, the tendency to "conflict" diminishes.; When costs and benefits reach some kind of equilibrium, "cooperation" tends to rise and gradually leads to spontaneous order. Although this spontaneous order has its limitations due to the limited rationality of its participants, it still can play a positive role in the development of urban public space. In the concluding section, the paper proposes an optimization strategy of interest integration and coordination for urban space development, which may be of reference value for architects and government management to actively guide this spontaneous order in urban planning and urban governance.